Cutting management of alley cropped leucaena/gliricidia - guinea grass mixtures for forage production in southwestern Nigeria - Ezenwa, I.; Reynolds, L.; Akenova, M.E.; Atta-Krah, A.N.; Cobbina, J. (Springer, 1995)
A study was conducted at Fasola in southwest Nigeria to determine the best tree cutting scheme for forage production and the effects of hedge configurations on tree, grass and total forage productivity of 6-8 year-old leucaena (Leucaena leucocephala Lam. de Wit) and gliricidia (Gliricidia sepium Walp.) - Guinea grass (Panicum maximum jacq. cNtchisi) mixture. After a uniform cut at the end of January 1990 (mid-dry season), the trees were cut according to the following cutting regimes; one cut after a 12-month regrowth (12M); two cuts after three - and nine-month regrowth (9-3M); three cuts, two cuts every three months and the third cut after a six-month regrowth (3-3-6M), and four cuts every three months (3-3-3-3M). Grass was cut every six weeks between April and October followed by a cut in January. The hedge configuration was either one or three hedgerows of mixed stands of leucaena and gliricidia. There were twice as many trees and one-third less grass in the triple than in the single hedgerow hedge configuration. The 3-3-3-3M, 9-3M and 3-3-6M cutting regimes produced the highest total forage (tree foliage + grass) dry matter yields (DM) of 6.54, 5.80 and 5.77 t DM ha-1 annum-1, respectively. The magnitude of the difference between the tree forage yields of the triple and single hedgerow plots (16 percent) did not reflect the theoretical difference in the number of trees (33 percent) in the two arrangements.